2011
DOI: 10.32635/2176-9745.rbc.2011v57n3.667
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida em Tabagistas que Buscaram Auxílio para Deixar de Fumar por meio de Aconselhamento Telefônico

Abstract: Introdução: Diversos fatores podem interferir na qualidade de vida, entre eles os problemas advindos do uso de substâncias, como o tabaco, que por consequência afetam a satisfação com a vida. Os efeitos do tabagismo, que interferem na qualidade de vida, servem para alertar o tabagista, bem como motivá-lo a parar e manter a abstinência. Objetivo: Avaliar a qualidade de vida por meio do WHOQOL-Bref em tabagistas que procuraram um serviço de teleatendimento para informações e orientações sobre drogas. Método: Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These findings were almost similar with these studies. 11,13,14 The study result showed that in the last 30 days, the majority of the respondents had physical pain (57.9%), had sleeping disturbance(66.4%), had nausea(54.8%), had lack of energy or tiredness(80.4%), had depression(89.4%), had aggressiveness(84.2%), had recalling problem(70.6%), had auditory-visual hallucinations(27.7%), had concentration problems(78.3%), had disorientation problems(44.0%), use of illicit drug to feel better physically(69.8%), used of illicit drug to feel better mentally(70.6%), and had physical pain which hampered daily activities(73.2%). The majority respondents felt of deterioration of physical condition (91.1%), and felt of deterioration of mental condition (89.8%), getting care from surrounding people (95.7%), had family problems (64.3%), absolutely believed that if drug use reduce social activities (57.9%), and respondents absolutely believed that if some people can quit drug use (69.8%).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were almost similar with these studies. 11,13,14 The study result showed that in the last 30 days, the majority of the respondents had physical pain (57.9%), had sleeping disturbance(66.4%), had nausea(54.8%), had lack of energy or tiredness(80.4%), had depression(89.4%), had aggressiveness(84.2%), had recalling problem(70.6%), had auditory-visual hallucinations(27.7%), had concentration problems(78.3%), had disorientation problems(44.0%), use of illicit drug to feel better physically(69.8%), used of illicit drug to feel better mentally(70.6%), and had physical pain which hampered daily activities(73.2%). The majority respondents felt of deterioration of physical condition (91.1%), and felt of deterioration of mental condition (89.8%), getting care from surrounding people (95.7%), had family problems (64.3%), absolutely believed that if drug use reduce social activities (57.9%), and respondents absolutely believed that if some people can quit drug use (69.8%).…”
Section: Discussionmentioning
confidence: 99%